A Short Review of Mukhdushika Disease. - Tetarwal, Poonam; Samagandi, Kashinath; Sharma, Kamalesh Kumar (International Research Journal of Ayurveda & Yoga, 2023)
People are most conscious and careful about beauty of face. Mukhdushika, as its name suggests disfigurement of face as it hampers beauty. Being Khudra roga it was not well explained in samhita neither its samprapti was given so, here is an attempt to hypothesis its samprapti as well description on the basis of the details in samhita. Acne is its counterpart in modern text and it is a disease of Pilosebaceous unit (PSU). Here comparison is made between modern pathogenesis of acne with Mukhdushika which may lead to conclusion that swedavaha strotas may have some connection with Pilosebaceous unit (PSU).